Molecular Docking of the Cannabis sativa L. Bioactive Compound Against Inflammation Induced by Cigarette Smoke Exposure (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2023)
Cigarette smoke can modulate and increase chronic inflammation of the respiratory tract. The constituents of cigarette smoke-induced inflammation can activate several cell signaling pathways, including mitogen-activated protein kinases (MAPK), nuclear factor kappa-B (NF-κB), signal transducer and activator of transcription (STAT), and activatory protein-1 (AP-1). Cannabis plant (Cannabis sativa L.) contains many phytochemical compounds including cannabinoids, terpenes and phenolic compounds, which have potential in medicine, one of them is as an anti-inflammatory. This study aims to determine the interactions formed between bioactive compounds from cannabis plants in anti-inflammatory activity caused by cigarette smoke induction in the JAK/STAT and MAPK pathways through a study in silico. This research method was carried out in a descriptive exploratory manner using online databases such as PubChem, PASS online, SEA (Similarity Ensemble Approach) and Swiss Target Prediction, STRING. Docking simulation was carried out using PyRx 0.8. Data from software and web devices were analyzed descriptively and compared with control compounds. The docking results show that the compounds from Cannabis sativa L. can act as an anti-inflammatory in the context of cigarette smoke-induced inflammation. This is indicated by the similarity of amino acid residues resulting from the interaction of the aspirin drug (control) with the anti-inflammatory receptor protein in the compound cannabidihydrophenanthrene with PDGFRA and KDR receptors and compounds cannabicyclol with AKT1 and KDR receptors. This is indicated by the presence of value affinity is low indicating a stable and strong bond.